Exploring the Potential of Cooperative Education Students from the Corporation Perspective to Enhance Cooperative and Work-Integrated Education (CWIE): A Case Study of Prince of Songkla University, Phuket Campus - Sangtong, Kamonwan; Tongtep, Nattapong (Journal of Information and Learning [JIL], 2023)
In contemporary higher education, many institutions are actively promoting cooperative and work integrated education (CWIE), recognizing its pivotal role in preparing students for the realities of the professional world upon graduation. This policy involves sending students to work within corporations and equipping them with the skills and readiness needed for success in their future careers. The primary objective of this study is to assess the potential of Cooperative Education students from the perspective of corporations, particularly focusing on the CWIE management system encompassing both soft and hard skills. The study draws upon data collected over a three-year period (academic years 2020-2022) from 360 different corporations where students from Prince of Songkla University’s Phuket Campus engaged in Cooperative Education programs. Data analysis employed a range of statistical techniques, including descriptive statistics, frequency distribution, mean, standard deviation, and percentage calculations. The research findings indicate that, according to corporate assessments, Cooperative Education students demonstrate commendable proficiency in social skills (soft skills) and knowledge-based skills (hard skills), rated between an average of 3.50 and 4.49 on a scale of 5. These results underscore corporations’ recognition of the potential exhibited by Cooperative Education students from Prince of Songkla University, Phuket Campus, and their alignment with the labor market’s demands. The insights gained from this research can serve as a valuable resource for enhancing teaching and learning practices, ultimately producing graduates who are better suited to meet the evolving requirements of the labor market. This endeavor contributes to the realization of the university’s strategic plan and the ongoing pursuit of positive outcomes.